2018
DOI: 10.1007/s11661-018-4912-9
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Effect of a Paint Bake Cycle on the Microstructure–Mechanical Properties Relationship of a Resistance Spot Welded Advanced High Strength Steel

Abstract: The effect of an automotive paint bake (PB) thermal cycle on the microstructural evolution and the mechanical properties of resistance spot welded advanced high strength steel is presented in this work. Mechanical behavior of the heat-treated welds reveals an increase in maximum cross-tension strength, displacement and subsequently energy absorption capability when 453 K (180°C)-20 minutes a bake thermal cycle is applied after welding. The microstructures of resistance spot welds with and without a PB heat tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…It should be noted that the load-displacement behavior of the AWS-PB sample exhibits a strong resemblance to load-displacement curves documented in the literature. 32,33) In Region 1, both the AWS and AWS-PB samples exhibit extensive bending of the base material, which is widely accepted in the literature. 30) In Region 2 (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…It should be noted that the load-displacement behavior of the AWS-PB sample exhibits a strong resemblance to load-displacement curves documented in the literature. 32,33) In Region 1, both the AWS and AWS-PB samples exhibit extensive bending of the base material, which is widely accepted in the literature. 30) In Region 2 (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Electrode force, welding time, and holding time were kept constant at 5.5 kN, 0.24, and 0.2 s, respectively, according to the base material's thickness, strength, and AWS D8.9 Standard. According to previous works, [34,35] , baking heat treatment after resistance spot welding can improve the mechanical properties of AHSS resistance spot welds. However, in this study, no post-weld baking was conducted after welding.…”
Section: Methodsmentioning
confidence: 94%
“…As a number of Al alloys such as 6xxx and 7xxx series alloys are characteristically temper age hardened, the effect of post-weld baking on base metal strength and the joint performance has been a subject of many studies, on both steel-steel RSWs and Al-Al RSWs. For example, in high strength steel RSWs, it has been found that post-weld baking resulted in increased cross-tension strength and fracture toughness, due to the low-temperature baking induced precipitation of carbides in martensite within weld nugget and heat affected zone (HAZ) [1][2][3][4]. For the heat treatable Al alloys, it is well acknowledged that paint baking hardens the materials through precipitation strengthening, however, for the corresponding RSWs, the post-weld baking was found to have limited influence on the joint strength.…”
Section: Introductionmentioning
confidence: 99%